2004
DOI: 10.1038/sj.pcan.4500756
|View full text |Cite
|
Sign up to set email alerts
|

Role of transition zone sampling by TURP in patients with raised PSA and multiple negative transrectal ultrasound-guided prostatic biopsies

Abstract: The purpose of the study was to determine the role of transurethral resection of the prostate (TURP) to detect prostate cancer in patients with consistently negative transrectal ultrasound-guided biopsies of the prostate. We retrospectively identified and analysed the patients who also had at least two sets of transrectal ultrasound guided sextant prostate biopsies before their TURP during the period between 1998 and 2002. A total of 14 such patients were identified and the outcome of TURP was analysed. Three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 24 publications
(21 reference statements)
0
9
0
Order By: Relevance
“…23 However, a consistent number of PCa, not found by biopsy, are subsequently diagnosed by TURP or open adenomectomy. For this reason, after multiple negative biopsy series, some authors have suggested to perform a TURP, even in men not complaining LUTS: Radhakrishnan et al 24 Zigeuner et al 25 and Puppo et al 3 reported a PCa detection after TURP of 21, 7.9 and 42.8%, respectively. Recently, van Renterghem et al 26 in 82 patients with minor LUTS but elevated PSA levels evaluated the clinical benefits of TURP by assessing its effect on IPSS, PSA levels and cancer detection rate: they reported an incidental PCa in 9.8% of cases, whereas PSA levels and IPSS score in patients with BPH decreased to 1.1 and 1.5 ng ml À1 , respectively.…”
Section: Discussionmentioning
confidence: 99%
“…23 However, a consistent number of PCa, not found by biopsy, are subsequently diagnosed by TURP or open adenomectomy. For this reason, after multiple negative biopsy series, some authors have suggested to perform a TURP, even in men not complaining LUTS: Radhakrishnan et al 24 Zigeuner et al 25 and Puppo et al 3 reported a PCa detection after TURP of 21, 7.9 and 42.8%, respectively. Recently, van Renterghem et al 26 in 82 patients with minor LUTS but elevated PSA levels evaluated the clinical benefits of TURP by assessing its effect on IPSS, PSA levels and cancer detection rate: they reported an incidental PCa in 9.8% of cases, whereas PSA levels and IPSS score in patients with BPH decreased to 1.1 and 1.5 ng ml À1 , respectively.…”
Section: Discussionmentioning
confidence: 99%
“…However, the long-term follow-up of these patients remains unclear. Furthermore, the benefit of transition zone sampling by TURP in patients with rising PSA levels and multiple negative peripheral zone biopsies has been demonstrated [27] . In another study, it was concluded that BOO should not interfere when considering TURP as a treatment option [28] .…”
Section: Discussionmentioning
confidence: 99%
“…In the daily urological practice, we frequently meet patients with increased PSA levels and negative prostate biopsies [2]. In spite of re-biopsies, the histopathological findings still remain negative, and the patient presents bladder outlet obstruction.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of prostate cancer has increased with the use of prostate specific antigen (PSA) and the digital rectal examination as screening procedures for prostate cancer [1,2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation